Beras Analog: Solusi Tepat Guna Olahan dari Jagung, Labu Kuning dan Kulit Pisang - Herawati, Reni; Faizah, Siti; Bimantara, Bingar; Supriyanto, Supriyanto (Universitas Trunojoyo Madura, 2022)
Stunting is a stunted development of the brain and body of toddlers due to malnutrition since the first 1000 days of life. Stunting is a problem because toddlers grow up as the nation's successors. Fulfillment of toddler nutrition can be by consuming analog rice. The purpose of the study was to determine the best analog rice formulation from corn flour, banana peel flour and pumpkin flour and the characteristics of analog rice from physical, chemical and amino acid tests. The research method used RAL (Completely Randomized Design). The formulations of corn flour, pumpkin flour and banana peel flour were divided into 3 levels, namely the ratio (6:2:2), (6:2:1), (6:1:2). The addition of water consists of 2 levels, namely 1:1 and 1:1.5. The best analog rice was the result of sensory test followed by physical, chemical and amino acid tests. The results showed the best formulation (6:2:1) with the addition of water 1:1.5. The color test shows an average brightness of 15.56-22.239, an average redness of 5.319-8.800, an average yellowness of 28.222-29.933. Texture test obtained hardness value of 79.511 N, adhesiveness 0.119 N, Cohesiviness of 1.141 and fracturability of 2.4493 and springiness of 0.541. The value of water content is 7.21%, protein is 10.98%, carbohydrates is 73.81%, vitamin A is 67.501%, amino acids are isoleucine content is 45.60 mg/g, leucine is 118.87 mg/g, lysine is 38.91 mg/g. g, methionine 18.24 mg/g, threonine 52.00 mg/g, valine 56.16 mg/g, and phenylalanine 72.35 mg/g.